“Dosis de ácido -3- indolbutirico y tipo de estaquilla en el enraizamiento de plukeneita brachybotrya (Muller. Arg., 1865) en la provincia de San Martín” - Amasifuen Ramirez, Miguel Ángel (2015)
In order to evaluate the rooting juvenile cuttings of Plukenetia brachybotrya (Müller. Arg., 1865 ), under the effect of four doses of acid indole -3 - butyric acid (O%, 0.2 %, 0.4 %, O, 6%), and three types of cuttings (basal • middle and apicaJ ) using propagators sub irrigation. The experimental nursery of the Research lnstitute of Peruvian Amazon (llAP) - San Martín was the trial site; using a completely randomized design with a factorial arrangement 4A x 38, with three replicates and twelve cuttings per experimental unit. Rooting percentages AIB at a dose of 0.2% with 91% obtained at the end of the trial (30 days to settle in the propagator). In addition, that the type of basal, middle and apical cuttings showed no statisticaJ difference in their development, overall species can be easily rooted for the work of clonal propagation. Keywords: Plukenetia brachybotrya, vegetative propagation, rooting juvenile cuttings, cutting length, leaf area, sub chamber irrigation.